Accelerating the advancement of black women leaders in corporate South Africa - Letsoalo, Shamiela (University of the Witwatersrand, Johannesburg, 2024)
As of 2022, the disparity in corporate South Africa's top management positions were evident, with only 11% of Black women holding such roles, contrasting starkly with the 53.1% representation of white males in similar positions. Examining the progression over the preceding four years, the data from 2017 reveals that Black women occupied 14.2% of board positions, indicating a modest 6% increase during that period. This information substantiates the observation that Black women face substantial underrepresentation in high-ranking corporate roles within South Africa and that their advancement to these positions has been notably sluggish. The study's theoretical framework employed a comprehensive approach by integrating three interconnected perspectives: Intersectionality Theory, Organisational Leadership Theories, and Marxist Feminist Theory. This triangulation offered a nuanced exploration of the factors influencing the acceleration of Black women leaders to top positions. A deliberate selection process involved choosing 8 Black women leaders from 7 companies and 1 state-owned entity for participation in this study. The selected individuals participated in either face-to-face interviews or virtual open-ended question sessions through video conferencing platforms, Zoom or Microsoft Teams. During these interactions, the participants candidly discussed their career paths to executive positions, highlighted obstacles faced during their journeys, and reflected on the strategies that enabled them to overcome challenges in their pursuit of leadership roles. The participants described the challenges they encountered which in their view impeded their progress in pursuit of career advancement to senior and top management positions. The study delved into the professional journeys of these accomplished Black women leaders through semi-structured interviews. Targeting c-suite and senior-level professionals, including CEOs, CFOs, COOs, and group executives, the research explored their experiences across diverse sectors such as financial services, professional consulting, technology, government entities, and mining. All participants, who were situated in Cape Town and Johannesburg in South Africa, were deliberately selected from the researcher's professional and personal network. Purposive sampling ensured representation from various leadership roles. This qualitative exploration, rooted in the participants' lived experiences, uncovered insights into systemic barriers, and organisational initiatives affecting the accelerated progress of Black women leaders to senior and executive positions, and the strategies which supported them in their advancement to leadership roles. The study's approach provided more information on the lived experiences of the participants, urging further research and interventions to enhance and accelerate the representation of Black women in senior corporate positions in South Africa. The study addressed a pressing issue of transformation and diversity in corporate South Africa by offering practical solutions for Black women leaders and companies. It emphasised the significance of actively building and nurturing professional networks, mentorship, and continuous learning as pivotal strategies for Black women navigating corporate landscapes. Additionally, for companies aiming to foster diversity and inclusion, the study underscored the importance of clear communication of policies, effective mentorship and sponsorship programmes, and the promotion of an inclusive organisational culture. Providing flexible work arrangements to support work-life balance and addressing specific challenges faced by Black women leaders were identified as key contributors to a supportive environment. The study concludes by recognising its role as a foundational exploration, shedding light on the challenges faced by Black women leaders in corporate South Africa, offering solutions, and serving as a baseline for further in-depth investigation
A Research Proposal submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg 2024
Keywords: Black women; Leaders; Corporate South Africa; Career advancement; UCTD; SDG-5: Gender equality